Problems of Irreversibility in the Control of Persistent Pollutants - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1989)
This paper deals with two different types of irreversibility: Pollution irreversibility occurs if the stock of pollution cannot be reduced (any more) by nature's assimilative capacity; characteristics irreversibility occurs when some characteristic of the environmental resource is irreversibly lost as soon as the environmental degradation exceeds a certain threshold level. For both cases the optimal intertemporal strategy of pollution control is characterised under conditions of certainty. Then the issue of characteristics uncertainty is further investigated under the assumption that the social evaluation of the resource characteristic is uncertain. Moreover, if there is the prospect of better information at some future point in time, it is shown that an unwarranted anti-preservation bias in pollution management is introduced by the decision maker if he or she ignores the future emergence of new information. A numerical example clarifies the value of new information, known in the literature as the quasi-option value.
Keywords: 330